2011
DOI: 10.1186/1465-9921-12-50
|View full text |Cite
|
Sign up to set email alerts
|

High blood pressure, antihypertensive medication and lung function in a general adult population

Abstract: BackgroundSeveral studies showed that blood pressure and lung function are associated. Additionally, a potential effect of antihypertensive medication, especially beta-blockers, on lung function has been discussed. However, side effects of beta-blockers have been investigated mainly in patients with already reduced lung function. Thus, aim of this analysis is to determine whether hypertension and antihypertensive medication have an adverse effect on lung function in a general adult population.MethodsWithin the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 24 publications
5
21
0
Order By: Relevance
“…These findings are in line with previous observations, although the mechanism is still unclear. Schnabel et al 23 reported an association between both high blood pressure and the use of beta-blockers with impaired lung function. We did not investigate the use of antihypertensive agents, and cannot precisely explain the mechanism underlying the association between the systolic blood pressure and lung function in men.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with previous observations, although the mechanism is still unclear. Schnabel et al 23 reported an association between both high blood pressure and the use of beta-blockers with impaired lung function. We did not investigate the use of antihypertensive agents, and cannot precisely explain the mechanism underlying the association between the systolic blood pressure and lung function in men.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both pulmonary disease and systemic blood pressure are associated with biomass fuel use, yet the interaction between pulmonary function and systemic blood pressure in the setting of biomass fuel use has not been adequately characterized. While several large cohort studies have described an association between reduced lung function with blood pressure and arterial elasticity, it remains unclear whether cardiovascular disease from HAP occurs with concomitant reduced lung function 1215 . We sought to determine the association between daily biomass fuel use with systemic blood pressure, prehypertension and hypertension in a population-based cohort of adults in Puno, Peru and if lung function, as measured by spirometry, was an effect modifier of the relationship between daily biomass fuel use and systemic blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have shown similar results of the relationship between lung function and hypertension after adjusting for potential confounders [9,12,[27][28]. Schnabel et al [9] reported that high blood pressure was associated with reduced lung function (for both % predicted FVC and FEV 1 ) in general adult population adjusting for gender and other covariates. In contrast to our study, Margretardottir et al [12] found that significantly stronger inverse association between FVC and hypertension in men than in women.…”
Section: Discussionmentioning
confidence: 77%
“…Numerous studies [1][2][3][4][5][6][7] have demonstrated that blood pressure is a risk factor for future cardiovascular diseases. Also these studies have shown that persons with lower pulmonary function indicators, forced expiratory volume in one second (FEV 1 ) [2,[4][5][8][9], forced vital capacity (FVC) [6][7][8][9] and FEV 1 /FVC ratio [3] have a higher risk for developing cardiovascular diseases including hypertension. There may be several possible pathophysiological mechanisms for these associations including impaired left ventricular performance and cigarette smoking.…”
Section: Introductionmentioning
confidence: 99%